Impact of Selected Behavioral and Environmental Factors on the Antibiotic Therapy in Polish Children With Upper Respiratory Tract Infections - Ślęzak, Katarzyna; Dembiński, Łukasz; Konefał, Artur; Dąbrowski, Mikołaj; Mazur, Artur; Peregud-Pogorzelska, Małgorzata; Wawrykow, Paweł; Konefał, Dorota; Peregud-Pogorzelski, Jarosław (Frontiers in Pediatrics, 2021)
Antibiotic therapy must be carried out consistently and according to the guidelines. Viruses are the dominant cause of upper respiratory tract infections (URTIs) in children, as has been shown in many previous studies. Unnecessary antibiotic therapy should be avoided so that it does not affect patients’ health and lead to the development of resistant bacterial strains. Here we report a national survey conducted in a group of 4,389 children to assess the impact of selected behavioral and environmental factors on antibiotic therapy in patients with URTIs. We found that selected environmental factors influenced the type of treatment. The place of residence, having siblings, an absence of vaccinations, the presence of allergies, and attendance at educational institutions were conducive to antibiotic therapy. These factors also influenced the frequency of hospitalization of children and their absence from nurseries, kindergartens, and schools, as well as the absence of their guardians from work.